Hemodynamic effect of Neuroform stent on intimal hyperplasia and thrombus formation in a carotid aneurysm - Jou, Liang-Der (2011)
Stents play an important role in management of cerebral aneurysms. A stent reconstructs the parent artery, assists coil embolization, and decreases flow activity within an aneurysm. However, an in-stent stenosis often occurs within the stented artery and compromises the circulation at the parent artery. Hemodynamic basis of re-stenoses from aneurysm stenting is not fully understood. An 8 mm cavernous carotid aneurysm with a wide neck was treated by a Neuroform stent first and by coils five weeks later. A comparison of the difference in morphology during this five-week period reveals the presence of intimal hyperplasia in the internal carotid artery, 1.3 mm thick at the proximal end and 1 mm at the distal end of the stent, and 1 mm thick thrombus at the postero-inferior side of the aneurysm. Computational fluid dynamic analyses show that the site of intimal hyperplasia is exposed to low wall shear with high oscillatory shear index (OSI), and the location of thrombus is subject to high OSI. Intimal hyperplasia and thrombus occur at comparable rates, but at different hemodynamic conditions; however, both prefer regions with high OSIs.